Phospholipid content in the compact and spongious musculature of the carp heart (Cyprinus carpio) - Drnková, J; Nováková, O; Pelouch, V; Ostádal, B; Kubista, V (Physiologia Bohemoslovaca, 1985)
The phospholipid content of the spongious and compact musculature of the heart of the carp (Cyprinus carpio) was compared. The content of phospholipids is higher in the spongious musculature, the greatest difference being in the content of diphosphatidylglycerol: 2.53 mumol P . g-1 wet weight in the spongious layer and 1.29 mumol P . g-1 wet weight in the compact one. In both tissues plasmalogens represent 20-27% of the tissue content of choline and ethanolamine phosphoglycerides.
Keywords: Carps; myokard; kardiolipiny; fosfolipidy; tkáňová distribuce; Animals; Cardiolipins; Myocardium; Tissue Distribution; zvířata; Heart; Phospholipids; kapři; srdce; Cyprinidae